Effect of long-term storage of malting barley on malt quality - Sychra, Luboš; Psota, Vratislav; Mareček, Jan (BrewingScience, 2001)
Long-term storage of qualitative batches of malting barley for gradual consumption is one of possibilities how to ensure the uniform quality of grain for storage. Changes were recorded in samples of long-term stored malting barley varieties Akcent, Kompakt, Krona, Olbram and Rubín by means of parameters of produced malt (extract, relative extract at 45 ºC, Kolbach index, diastatic power, apparent final attenuation, friability, -glucan content in malt extract, protein content in malt) in regular intervals for two years. At the beginning of the storage period, the malting barley was subjected to controlled ventilation and then the malting barley grain was stored without any active ventilation. It follows from the analysis that the long-term storage results particularly in the decreased activity of amylolytic and cytolytic enzymes, which results in the deterioration of malt extract quality. By using regression equations it is possible – on the basis of the knowledge of initial quality of malt made of malting barley – to predict the quality development during storage.